(untitled) (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Achievement emotions have been shown to mediate the association between achievement goals and learning performance, but no research to date has tested whether there is a similar process in predicting germane cognitive load. Based on the control-value theory of academic emotions (Pekrun, 2006), the present study tested a model to determine whether goal orientation and extraneous load were mediated by achievement emotions in predicting germane load. Methodology – This survey study involved 487 voluntary university students (N = 487; 61% women; ages 17-23) who were enrolled in a statistics class and these study participants were selected using the cluster random sampling technique. They responded to three adapted scales which were translated into Bahasa Indonesia. The scales were, namely the Achievement Goal Questionnaire (AGQ), Achievement Emotions Questionnaire (AEQ), and Cognitive Load Questionnaire. Data were collected 20 minutes before the statistics class ended and the data was then analyzed using bootstraped bias corrected (CI = 95%; N=5000) in Structural Equation Modelling (SEM). Findings – The results of the structural equation modeling indicated that a mastery-approach goal was associated with higher germane load through higher enjoyment and lower anxiety, and a performance-avoidant goal was associated with lower germane load through higher anxiety. Moreover, extraneous load was negatively associated with germane load through enjoyment, but was positively associated with germane load through anxiety. Significance – These findings have implications in educational settings: for most students with a mastery-approach goal, and enjoyable activities are helpful, as with those that increase cognitive performance in processing learning information. The present research is the first study to show that achievement goals are linked to the capacity to process learning-relevant information, in part due to the emotions the student experiences in the learning environment.